The effectiveness of promotion through advertising to gain sustainable event management based on youth in Klang Valley / Rabiatul Masturah Zainal and Zafirah Aiza Abdul Aziz - Zainal, Rabiatul Masturah; Abdul Aziz, Zafirah Aiza (2015)
This research study aim to assess the effectiveness of advertising aspects which involve the advertising tools on sustainable event management based on youth in Klang Valley. The advertising tools or methods that usually use by an event organizer to promote their events are through television, radio, Internet, printed advertisement and outdoor advertisement. We are trying to discover which of these advertising methods able to give huge impact on sustainability of event management based on youth in Kalang Valley. We targeted youth age range from 15 – 24 years old in Klang Valley to be our respondents for our research. This range of age is based on the definition of youth gave by United Nations Educational, Scientific, and Cultural Organization (UNESCO). We are using convenience sampling and we did distribute the questionnaire to the youth visitors at Royal Floria Putrajaya 2015. We were also distribute using Google Form to our target respondents. We managed to get 153 participation from our target respondents. From the findings that we obtained, we are able to answer our research questions which event advertisement should be more on television as it give more impact to sustain event management. Besides, we also know that 38% of the respondents able to remember the event advertisement for a week. As for preliminary research, we were able to get an accepted value in our reliability test (Cronbach’s Alpha) which for television, the results is 0.552. It is also showed that by advertising an event through television, the event organizer can ensure the high level of sustainability of event management. This research can be proceed with the same research topic but in large scale to get more precise results.